Identifikasi Kesesuaian Kurikulum Manajemen Konstruksi dan Rencana Anggaran Biaya Program Studi PTB UNJ Terhadap Kompetensi Kerja Quantity Surveyor Bidang Konstruksi - Bima Garyn Destyawan; Santoso Sri Handoyo; Anisah (Universitas Serambi Mekkah, 2025)
This research aims to determine the level of relevance between the Construction Management and Budget Plan curriculum in the Construction Engineering Education Study Program, Faculty of Engineering, UNJ, and the work competencies of Construction Quantity Surveyors. This study uses a quantitative descriptive method. The data analysis results show that the relevance level between the Construction Management Course Learning Outcomes (CLOs) and Quantity Surveyor competencies is 51.5%, while between the Budget Plan CLOs and Quantity Surveyor competencies it is 72.7%. Among the Construction Management CLO indicators, the concept of Earned Value (calculating BCWP, BCWS, ACWP, CV, SV, PI) is the most relevant indicator to Quantity Surveyor competencies. Among the Budget Plan CLO indicators, 'Students calculate the BOQ and Recap for a simple house construction project' is the most relevant indicator to Quantity Surveyor competencies. Based on these results, the Construction Management and Budget Plan curriculum of the Construction Engineering Education Study Program at Jakarta State University is Moderately Relevant (MR) to the work competencies of Construction Quantity Surveyors.